Integration of Dalihan Natolu's Local Wisdom in the Sets Learning Model to Improve Student's Problem Solving Ability - Siagian, Gunaria; Yohandri, Yohandri; Razak, Abdul (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study integrates the Science, Environment, Technology, and Society (SETS) learning model with the cultural framework of Dalihan Natolu (DNT), aimed at fostering active, effective, and creative learning. The objective was to examine the impact of this integrated DNT-SETS approach on students’ problem-solving skills, particularly in the context of environmental pollution. A quasi-experimental design was employed, involving 60 students from SMA GKPS Pematang Raya, divided into an experimental group (30 students) and a control group (30 students). The learning materials included lesson plans, student worksheets, learning model guides, and six essay questions related to environmental pollution, designed to assess problem-solving skills. Data were analyzed using the Kolmogorov-Smirnov test for normality and Levene's test for variance homogeneity, both at a 5% significance level. A t-test was conducted to determine the effectiveness of the DNT-SETS model. The t-test results showed a significance value of 0.000, indicating a statistically significant difference between the experimental and control groups. The experimental group, which used the DNT-SETS model, demonstrated a 59% improvement in problem-solving skills, compared to a 38% gain in the control group. This suggests the DNT-SETS model effectively enhanced students' abilities to address environmental issues. The integration of the DNT-SETS model enabled students to approach environmental problems holistically, linking scientific concepts with real-world challenges. This model encourages students to gather evidence and develop effective solutions based on their understanding. The DNT-SETS model significantly improves problem-solving skills in environmental education, offering a practical and culturally relevant teaching strategy.